Nail Psoriasis Quality Of Life Scale 10 (Npq10) As A Predictor Of Quality Of Life In Nail Psoriasis Patients - Oktavriana, Triasari; Febrianto, Bobby; Wijayanti, Niluh; Novriana , Dita Eka; Rosmarwati, Ervina; Kusumawardani, Arie (Journal Research of Social Science, Economics, and Management, 2022)
Nail psoriasis can affect the patient's quality of life, so to evaluate the quality of life in patients with skin diseases in general, the Dermatology Quality of Life Index (DLQI) can be used. The questionnaire was unable to distinguish the impact on quality of life caused by nail abnormalities or skin lesions, so a special scoring system was needed to evaluate the quality of life for nail psoriasis patients with the Nail Psoriasis Quality of Life Scale 10 (NPQ10). To find the relationship between the severity of nail posirais based on Nail Psoriasis Severity Index (NAPSI) score with DLQI and NPQ10. The total respondents were 20 people with a diagnosis of nail psoriasis who came to the Dermatovenereology Outpatient Clinic of Dr. Moewardi General Hospital, Surakarta from April-June 2020. We took photography and dermoscopy of fingernails and toes and then calculated the NAPSI score. All respondents filled out the DLQI and NPQ10 questionnaires. Pearson's (r) correlation test was used to find the relationship between the mean and standard deviations of NAPSI and DLQI and NPQ10. We also tested the correlation between DLQI and NPQ10. The data significance value was declared significant if p <0.05. The results of the correlation test between NAPSI scores with DLQI and NPQ10 showed a statistical relationship, where the correlation value between NAPSI and DLQI was slightly more significant than NPQ10 (r = 0.948: r = 0.877; p <0.05). The mean value of DLQI and NPQ10 in women was higher than men (14.12 ± 8.21: 11.5 ± 8.29 and 11.5 ± 3.58: 8.16 ± 4.52) with a correlation test value of DLQI and NPQ10 is r = 0.888, p <0.05. We found that the association between NAPSI correlates more significantly with DLQI than NPQ10. This may be due to some questions that do not reflect the daily activities of our study subjects, but NPQ10 score in women is higher than men where the quality of life for nail psoriasis is also influenced by gender.